Association between workaholism, vital exhaustion, and hair cortisol concentrations among teachers: A longitudinal study testing the moderation effect of neuroticism - Wettstein, Alexander; Schneider, Sandra; Jenni, Gabriel; Holtforth, Martin grosse; Tschacher, Wolfgang; La Marca, Roberto (Frontiers in Psychology, 2022)
Workaholism in teachers is characterized by the willingness to work until exhausted and may be associated with various adverse health outcomes as well as high economic costs. The present study examines the association between workaholism, vital exhaustion (VE), and hair cortisol concentration (HCC) as indicators of chronic stress. In addition, this study explores the moderating role of the personality trait of neuroticism on the relationship between workaholism and chronic stress indicators, i.e., VE and HCC. Forty-two [deleted for peer-review] teachers (28 females; Mage = 39.66, SD = 11.99) completed questionnaires assessing VE (Maastricht Vital Exhaustion Questionnaire), workaholism (Measure of Coping Capacity Questionnaire), and neuroticism (Big-Five Inventory). Together with VE, HCC was assessed twice, with a one-year lag. Both workaholism and neuroticism were positively associated with VE at both time points but not with HCC. Moderation analyses revealed a positive relationship between workaholism and VE in teachers with high neuroticism, while no such association was observed in teachers with low neuroticism. No associations were found between self-reports and HCC. These findings emphasize the importance of considering individual characteristics when investigating VE. Further research is necessary to investigate the applicability of HCC as a biomarker of chronic stress in the context of work.